1990
DOI: 10.1093/nar/18.12.3489
|View full text |Cite
|
Sign up to set email alerts
|

Three genes under different developmental control encode elongation factor 1-α inXenopus laevis

Abstract: We have cloned cDNAs encoding two variants of the elongation factor for protein synthesis in Xenopus laevis, called EF-1 alpha. One of these (42Sp50) is expressed exclusively in immature oocytes. It is one of two protein components of a 42S RNP particle that is very abundant in previtellogenic oocytes. The 42S RNP particle consists of various tRNAs, 5S RNA, 42Sp50 and a 5S RNA binding protein (42Sp43). A major function served by 42Sp50 appears to be the storage of tRNAs for later use in oogenesis and early emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Nevertheless, there are examples in multicellular eukaryotes of differential expression of isoforms of translation elongation factor 1A (eEF1A). In Drosophila and Xenopus, there is evidence that one EF1A gene is continuously expressed and one or two others are developmentally regulated (Hovemann et al, 1988, Djé et al, 1990. In mammals, the eEF1A2 gene is expressed in heart and muscle tissue and eventually becomes the only isoform expressed in these tissues (Knudsen et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are examples in multicellular eukaryotes of differential expression of isoforms of translation elongation factor 1A (eEF1A). In Drosophila and Xenopus, there is evidence that one EF1A gene is continuously expressed and one or two others are developmentally regulated (Hovemann et al, 1988, Djé et al, 1990. In mammals, the eEF1A2 gene is expressed in heart and muscle tissue and eventually becomes the only isoform expressed in these tissues (Knudsen et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear location may be associated with an interaction between eEF1A and the transcription factor ZPR1 (Gangwani et al 1998). A1, A3, and A4 have also been located at the plasma membrane, and may function in activation of PI4-Kinase (Yang et al 1993) or interaction with microtubules (Djé et al 1990) closely associated in the region. The A1 and A2 proteins were also localized to the vacuole.…”
Section: Expression Of Arabidopsis Eef1a In Comparison To Other Organmentioning
confidence: 99%
“…These genes were expressed in the ear, leaf, root, silk and stem tissues, but at diVerent levels. However, no evidence of tissue-speciWc or developmental-stage speciWc gene expression has been reported for eEF1A in plants (Kidou and Ejiri 1998;Carneiro et al 1999), results incongruent to those exhibited in animals (Djé et al 1990;Knudsen et al 1993;Kahns et al 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Two sequence-redundant eEF1A genes TEF1 and TEF2 are present in the yeast Saccharomyces cerevisiae [4,5]. In Drosophila melanogaster, two genes, F1 and F2, have been described (Hovemann et al [6]) while four and five eEF1A genes have been reported in Xenopus laevis and Solea senegalensis, respectively [7][8][9].…”
Section: Introductionmentioning
confidence: 99%